2016
DOI: 10.1098/rsif.2015.0974
|View full text |Cite
|
Sign up to set email alerts
|

A novel video-tracking system to quantify the behaviour of nocturnal mosquitoes attacking human hosts in the field

Abstract: Many vectors of malaria and other infections spend most of their adult life within human homes, the environment where they bloodfeed and rest, and where control has been most successful. Yet, knowledge of peri-domestic mosquito behaviour is limited, particularly how mosquitoes find and attack human hosts or how insecticides impact on behaviour. This is partly because technology for tracking mosquitoes in their natural habitats, traditional dwellings in disease-endemic countries, has never been available. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 28 publications
0
55
1
Order By: Relevance
“…The original approach to segmentation [5] used a difference image between consecutive frames and a single threshold value to identify movement. Whilst developing the RRS system, two issues were found.…”
Section: Signal Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…The original approach to segmentation [5] used a difference image between consecutive frames and a single threshold value to identify movement. Whilst developing the RRS system, two issues were found.…”
Section: Signal Processingmentioning
confidence: 99%
“…Large field of view back lit imaging systems have been reported with two parallel imaging channels to give a measurement volume of 2 x 2 x 1.4 m in total with large aperture Fresnel lenses enabling collimated illumination and telecentric imaging [5]. As part of this study, algorithms were also reported that produced flight tracks of 25 mosquitoes over hour long recording periods.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations